Effect of an active learning methodology combined with formative assessments on performance, test anxiety, and stress of university students - Cardozo, Lais Tono; Carvalho, Maeline Santos Morais; Costa, Rafaela; Lima, Patricia Oliveira de; Marcondes, Fernanda Klein; Azevedo, Maria Antonia Ramos de [UNESP] (American Physiological Society, 2020)
The aim of this study was to evaluate the effect of an active methodology combined with a lecture on undergraduate student learning and levels of stress and anxiety. The active learning methodology consisted of a lecture of 50-min duration, study at home with a textbook, an educational game activity, and three formative assessments on the topic of the cardiac cycle. In a following class, the students provided saliva samples to evaluate their levels of stress, received an anxiety test, and then undertook an exam to assess their understanding of the cardiac cycle. The traditional teaching methodology consisted of two lectures (~2-h duration) on blood pressure control systems, delivered orally. In the third class, the students provided saliva samples, received an anxiety test, and then undertook an exam to assess their understanding of blood pressure control systems. The level of stress was assessed with the concentrations of the stress biomarkers cortisol and alpha-amylase in saliva. Anxiety was assessed with the State-Trait Anxiety Inventory (STAI) questionnaire. The students achieved significantly higher average scores in exams when the active learning strategy was applied compared with the use of traditional theoretical classes. The active methodology resulted in significantly lower levels of stress and anxiety, as well as improved student performance, compared with the use of traditional lectures.
Keywords: active learning; active methodologies; educational game; formative evaluation; stress